La question de ľexistence dans la poésie De Jacques Crickillon - Švábenská, Denisa; Kyloušek, Petr, 1952-; Masarykova univerzita. Ústav románských jazyků a literatur (2005)
The work that I have done is to present the poesie of Jacques Crickillon and his own style that is so different. First I have presented his life that is so necesary (for his experiences, his travels) to understand his metode and philosophy that we meet in this poems. Then I wanted to presented his party analytic (like he works with figures, tropes) and show his style of the vers and poems. The moment after his presentation, the most importante is his own analyse of the thems that he is working and showing the themes usually speaking multiplicated by my own interpretation
Vedoucí práce: Petr Kyloušek
Bakalářská práce (Bc.)--Masarykova univerzita, Filozofická fakulta, 2005
Keywords: Crickillon, Jacques, -- 1940-2021; 20.-21. století; belgická poezie (francouzsky) -- 20.-21. století; existenciální poezie -- Belgie -- 20.-21. století; literárněvědné rozbory; existentialist poetry; literary criticism and history; bakalářské práce